(untitled) (The Pakistan Development Review, 2001)
In a Comment published in the Autumn 2000 issue of this journal, Mr Ghulam Soomro1 takes issue with our recent article in Population and Development Review.2 Although Mr Soomro is highly critical of our article, we are pleased that he has read the article carefully and made the effort to write an extended comment. We are not prepared, however, to concede the major points in that Comment. Two major points are made by him. First, that marital fertility decline is a small component of the recent fertility decline in Pakistan, which has been mainly due to postponement of entry to first marriage. Second, that the underlying motivation for fertility change in the 1990s has been economic distress, a consequence in part of the structural adjustment programmes instituted in the late 1980s. However, in the first point, Soomro interprets the demographic data from the past three decades incorrectly and, in the second point, he misrepresents our argument.